"My body was my temple": a narrative revealing body image experiences following treatment of a spinal cord injury. Issue 18 (28th August 2017) - Bailey, K. Alysse; Gammage, Kimberley L.; van Ingen, Cathy; Ditor, David S.
Abstract: Purpose: This narrative explores the lived experience of a young woman, Rebecca, and her transitioned body image after sustaining and being treated for a spinal cord injury. Method: Data were collected from a single semi-structured in-depth interview. Results: Rebecca disclosed her transitioned body image experiences after sustaining a spinal cord injury and being treated by medical staff immediately following her injury. Before her injury, she described a holistic body experience and named this experience her "temple". During intensive care in the hospital, she explained her body was treated as an object. The disconnected treatment of her body led to a loss of the private self, as she described her sacred body being stripped away – her "temple" lost and in ruins. Conclusions: Body image may be an overlooked component of health following a spinal cord injury. This narrative emphasizes the importance of unveiling body image experiences after the treatment of a spinal cord injury to medical professionals. Lessons of the importance of considering the transitioned body experiences after a spinal cord injury may help prevent body-related depression and other subsequent health impacts. Recommendations for best practice are provided. Implications for Rehabilitation:    Spinal Cord Injury    A spinal cord injury may drastically change a person's body image, thereby significantly impacting psychological health    More effective screening for body image within the medical/rehabilitation context is needed to help practitioners recognize distress    Practitioners should be prepared to refer clients to distress hotlines they may need once released from treatment